Identification of NY-BR-1-specific CD4+ T cell epitopes using HLA-transgenic mice - Gardyan, Adriane; Zörnig, Inka; Aulmann, Sebastian; Ruggiero, Eliana; Schmidt, Manfred; Halama, Niels; Kalle, Christof von; Schneeweiss, Andreas; Jäger, Dirk; Eichmüller, Stefan B. (International journal of Cancer Studies & Research, 2014)
Breast cancer represents the second most common cancer type worldwide and has remained the leading cause of cancer-related deaths among women. The differentiation antigen NY-BR-1 appears overexpressed in invasive mammary carcinomas compared to healthy breast tissue, thus representing a promising target antigen for T cell based tumor immunotherapy approaches. Since efficient immune attack of tumors depends on the activity of tumor antigen-specific CD4+ effector T cells, NY-BR-1 was screened for the presence of HLA-restricted CD4+ T cell epitopes that could be included in immunological treatment approaches. Upon NY-BR-1-specific DNA immunization of HLA-transgenic mice and functional ex vivo analysis, a panel of NY-BR-1-derived library peptides was determined that specifically stimulated IFNγ secretion among splenocytes of immunized mice. Following in silico analyses, four candidate epitopes were determined which were successfully used for peptide immunization to establish NY-BR-1-specific, HLA-DRB1*0301- or HLA-DRB1*0401-restricted CD4+ T cell lines from splenocytes of peptide immunized HLA-transgenic mice. Notably, all four CD4+ T cell lines recognized human HLA-DR-matched dendritic cells (DC) pulsed with lysates of NY-BR-1 expressing human tumor cells, demonstrating natural processing of these epitopes also within the human system. Finally, CD4+ T cells specific for all four CD4+ T cell epitopes were detectable among PBMC of breast cancer patients, showing that CD4+ T cell responses against the new epitopes are not deleted nor inactivated by self-tolerance mechanisms. Our results present the first NY-BR-1-specific HLA-DRB1*0301- and HLA-DRB1*0401-restricted T cell epitopes that could be exploited for therapeutic intervention against breast cancer.